Pemantauan dan Pengendalian Parameter Greenhouse Berbasis IoT Dengan Protokol MQTT - Eni Dwi Wardihani; Eka Ulia Sari; Helmy; Ari Sriyanto Nugroho; Yusnan Badruzzaman; Arif Nursyahid; Thomas Agung Setyawan; Media Fitri Isma Nugraha (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2024)
Modernization in the agricultural sector is expected to have an effect on improving the quality, production quantity, and continuity of the agricultural product supply. Currently, many smart agricultures are developed in greenhouses. However, several greenhouse parameters must be considered to optimize plant growth. This study has created a monitoring and control system for several Internet of things (IoT)-based greenhouse parameters, allowing farmers to monitor and control the greenhouse anytime and anywhere. It can also improve the work efficiency of farmers in monitoring and controlling, especially if there are multiple greenhouses to be monitored or controlled. The greenhouse monitoring data may be viewed in real time and stored on servers, making it easier for farmers to evaluate greenhouses and crops. The monitored parameters were greenhouse temperature, greenhouse humidity, and light intensity in the greenhouse, while the controlled parameters were greenhouse temperature and greenhouse humidity, using exhaust fans. The process of transmitting the greenhouse parameter monitoring and controlling data was carried out using the message queue telemetry transport (MQTT) protocol. Data loss and delay testing on the system was required to determine the reliability of the tool in the process of transmitting and receiving data. The quality of service (QoS) testing results was as follows: average data loss gateway-server monitoring was 10.6%, the average gateway-server monitoring delay was 1.9 s, and the average server-gateway control delay was 7.1 s. When the greenhouse temperature parameter value is less than the specified maximum threshold, the system turns on the drum fan so that the temperature reaches the minimum value at the threshold limit.